2018
DOI: 10.1038/s41467-018-07343-2
|View full text |Cite
|
Sign up to set email alerts
|

The structure and function of the global citrus rhizosphere microbiome

Abstract: Citrus is a globally important, perennial fruit crop whose rhizosphere microbiome is thought to play an important role in promoting citrus growth and health. Here, we report a comprehensive analysis of the structural and functional composition of the citrus rhizosphere microbiome. We use both amplicon and deep shotgun metagenomic sequencing of bulk soil and rhizosphere samples collected across distinct biogeographical regions from six continents. Predominant taxa include Proteobacteria, Actinobacteria, Acidoba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
290
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 382 publications
(313 citation statements)
references
References 77 publications
(143 reference statements)
21
290
0
2
Order By: Relevance
“…Rhizoplane, one of the root-associated layers, serves as a critical gate that regulates microbial entry into roots 49 . A comprehensive analysis indicated that no difference existed in the microbial community structure of rhizosphere and associated bulk soil samples collected from twelve citrus varieties which distributed on six continents 50 . In this study, the microbial community structure in roots was also similar to that in soil, suggesting that root-associated microbes were mainly derived from the soil biome 35 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rhizoplane, one of the root-associated layers, serves as a critical gate that regulates microbial entry into roots 49 . A comprehensive analysis indicated that no difference existed in the microbial community structure of rhizosphere and associated bulk soil samples collected from twelve citrus varieties which distributed on six continents 50 . In this study, the microbial community structure in roots was also similar to that in soil, suggesting that root-associated microbes were mainly derived from the soil biome 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the exudates containing sugars, organic acids and amino acids secreted by plant roots have strongly affected the composition of microbes in surrounding soil. Proteobacteria, Actinobacteria, Acidobacteria and Bacteroidetes have been reported as the primary consumers of plant exudates and the predominant taxa of citrus 50,51 . Other reports supported the above results and the microbial community of other plants including maize, arabidopsis and tamarix consists of a few dominant phyla, such as Proteobacteria, Actinobacteria, and Bacteroidetes 16,52,53 .…”
Section: Discussionmentioning
confidence: 99%
“…Using MetaBAT2 [14], an unsupervised MAG extraction tool, we recovered a high-quality MAG affiliated with the Cellvibrio genus, supported by both CheckM and AMPHORA2 results [15,16]. Cellvibrio is a crucial member of the citrus rhizosphere microbiome, as revealed by our global-scale citrus microbiome analysis, and is further enriched to the rhizoplane niche [6,13]. Therefore, we further refined this Cellvibrio MAG to assemble a high-quality genome [40] to investigate the strategies used for rhizoplane niche adaptation.…”
Section: Recovery and Curation Of The Almost Complete Metagenome-assementioning
confidence: 73%
“…Citrus rhizosphere microbiome are the microorganism closely attached to the rhizosphere, which plays an important role in promoting citrus growth and development. Xu et al suggested that plant-microbe interactions are very likely to be important factors that influence the assembly of rhizosphere microbiomes, such as bacterial secretion systems [40]. The enrichment of rhizosphere microbes can be attributed to their lifestyles [41][42].…”
Section: Discussionmentioning
confidence: 99%
“…Delgado-Baquerizo et al reported that only 2% of bacterial taxa made up nearly half of the soil bacteria at various sites around the world [43]. Meanwhile, Xu et al also found that there are only a few bacterial taxa, such as Proteobacteria, Actinobacteria, Acidobacteria, and Bacteroidetes, which are abundant in the citrus rhizosphere [40]. Similarly, we found that the dominant bacterial groups were Proteobacteria, Acidobacteria, and Actinobacteria in the citrus-cultivated rhizosphere soil, while the other bacterial groups were non-dominant bacteria.…”
Section: Discussionmentioning
confidence: 99%